Relapsing Depression in Paramedian Thalamic Infarctions - R. W. Baumgartner; T. Landis; M. Regard (Behavioural Neurology)
Depression has recently been associated with lesions in the CNS, particularly with large infarctions in the cerebral hemispheres. We report a patient in whom two episodes of acute depression were related to relapsing paramedian thalamic infarctions, which were accompanied by additional transient mild neuropsychological deficits, hypersomnia and a discrete sensory disturbance of the left face. Thalamic infarctions have been shown to mimic a variety of higher functional deficits, such as aphasias, apraxias and attentional disorders, traditionally associated with hemispheric strokes. We conjecture that the paramedian thalamic infarctions observed in our patient have in a similar manner been responsible for the transient depression.